Intermediate accounting - Weygandt, Jerry J.; Kieso, Donald E.; Warfield, Terry D. (New York : John Wiley & Sons, 2001)
This book is about: Financial accounting and accounting standards; Conceptual framework underlying financial accounting; The accounting information system; Income statement and related information; ...
Keywords: Accounting; Accounting